2013
DOI: 10.1093/cvr/cvt146
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage-derived hypoxia-inducible factor (HIF)-1α as a mediator of vascular remodelling

Abstract: Our results show that HIF-1α in macrophages plays a crucial role in promoting vascular inflammation and remodelling. As decreasing HIF-1α activity in macrophages may prevent the progression of vascular remodelling, HIF-1α may be a possible therapeutic target in vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…A,B), strongly suggesting that gut resident macrophages may be exposed to local changes in oxygen levels that could impact macrophage function. Previous studies suggest that exposure of macrophages to hypoxic conditions can induce expression of the transcription factor hypoxia‐inducible factor (HIF), a key regulator of cellular responses to hypoxic conditions . HIF1α in particular has recently been shown to be responsible for IFNγ expression in macrophages following exposure to hypoxic conditions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A,B), strongly suggesting that gut resident macrophages may be exposed to local changes in oxygen levels that could impact macrophage function. Previous studies suggest that exposure of macrophages to hypoxic conditions can induce expression of the transcription factor hypoxia‐inducible factor (HIF), a key regulator of cellular responses to hypoxic conditions . HIF1α in particular has recently been shown to be responsible for IFNγ expression in macrophages following exposure to hypoxic conditions .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that exposure of macrophages to hypoxic conditions can induce expression of the transcription factor hypoxia-inducible factor (HIF), a key regulator of cellular responses to hypoxic conditions. [50][51][52][53][54] HIF1α in particular has recently been shown to be responsible for IFNγ expression in macrophages following exposure to hypoxic conditions. 55 As a result, we next defined the impact of neonatal anemia on HIF1α expression in intestinal macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, in vivo studies do not always provide consistent findings. In a wire-induced vascular injury model, myeloid HIF-1α promotes vascular inflammation and remodeling manifested by increases in TNF-α and IL-6 levels proximal to the injury site and neointimal thickening of injured arteries (125). However, a recent in vivo genetic and drug-based approach suggested the opposite effect in a different mouse model, indicating that HIF-1α and HIF-2α accumulation correlates with reduced atherosclerosis development.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 99%
“…Moreover, myeloid-specific deletion of Hif-1α causes abnormalities in the motility, adhesion and invasiveness of peritoneal macrophages22. Interestingly, a recent study has suggested that HIF-1α plays a critical role in macrophages during vascular remodelling after femoral artery injury23. However, how HIF-1α regulates macrophage function during vascular development and blood vessel repair remains poorly understood.…”
mentioning
confidence: 99%